Effects of exercise on symptoms, vestibular/ocular motor screening and postural stability in a college-aged sample - Ryan N Moran; Nicholas G Murray; Michael R Esco; Ward Dobbs; Jamie McAllister-Deitrick (Concussion)
Aim: To examine the effects of maximal exercise on symptoms, vestibular/ocular motor screening (VOMS) and postural stability. Methodology: A total of 17 college-aged individuals completed a symptom scale, VOMS and the modified Clinical Test for Sensory Interaction and Balance (m-CTSIB), followed by a graded maximal exercise treadmill test. Assessments were repeated post exercise, 20 and 40 min post-exercise. Results: Significant increases in total symptoms, symptom severity scores and m-CTSIB scores from baseline to immediate post exercise were reported. Following 20-min recovery, improvements were noted on symptoms, visual motion sensitivity on VOMS and m-CTSIB. Conclusion: Symptoms and postural stability are influenced by exercise and following 20 min of rest, returned to baseline, indicating that a period of 20 min following a suspected concussion may be needed to negate exercise effects.